Mutual Assisting, Religion and moraliti value of Jumat Berkah in Stundet Perspective - Bahagia Bahagia; Leny Muniroh; Abdul Karim Halim; Rimun Wibowo; Rizkal Rizkal; Muhammad Shiddiq Ilham Noor (Universitas Pahlawan Tuanku Tambusai, 2022)
The mosque is a center of worship and the center of life. This study aims to find social, religious and moral values in Friday blessing activities. The research method used is descriptive qualitative method and purposive sampling. Data was collected by means of observation, documentation and in-depth interviews. The results showed that the improvement of worship and morals can be done with rewards in the form of food and drinks for children because inviting children to come to the mosque is a challenge. The provision of food and drink will make children not aware that they have worshiped so as to stimulate them in the future so that they continue to go to the mosque without any reward. In addition, there is a social value in which Friday's blessing is classified as an activity to help by providing food and drink to people who may be in trouble at that time. It is also a step in empowerment because the money from donors can be used to buy food and drink for worshipers who come to the mosque. Directly the activities of small and medium enterprises engaged in the food and beverage sector can be assisted through this activity. At the same time as an effort to increase the resilience of the community because during the pandemic many are having difficulties, with the blessing Friday, those who are having difficulties are not alone, the mosque is here to help them.